Phyto-Immunotherapy, a Complementary Therapeutic Option to Decrease Metastasis and Attack Breast Cancer Stem Cells - Fiorentino, Susana; Urueña, Claudia; Lasso, Paola; Prieto, Karol; Barreto, Alfonso (Frontiers in Oncology, 2020)
In this review, we report on the complexity of BCSCs as key cells in the emergence of a chemoresistant tumor phenotype, and as a result, the appearance of distant metastasis in breast cancer patients. The search for mechanisms that increase sensitivity to chemotherapy and also allow activation of the tumor-specific immune response is of high priority. As we observed throughout this review, natural products isolated or in standardized extracts, such as P2Et or others, could act synergistically, increasing tumor sensitivity to chemotherapy, recovering the tumor microenvironment, and participating in the induction of a specific immune response, which in the end would lead to the destruction of CSCs and the decrease in metastasis.